2014
DOI: 10.1136/bjophthalmol-2014-305564
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and survival among children with retinoblastoma in Uganda

Abstract: Diagnostic delay results in relatively high mortality among children with retinoblastoma in Uganda. There is an urgent need for more effective treatment modalities, particularly chemotherapy, and nationwide efforts to encourage earlier access to medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 11 publications
5
30
1
Order By: Relevance
“…Regarding gender and survival, the overall survival for the male child was found to be better than the female child in a previous study,22 although no such association was observed among our patients. On multivariate analysis, stage of the disease (intraocular versus extraocular) had a significant impact on the survival outcomes, which is consistent with previous studies that reported an association between severity of disease and the survival outcome 9 27 28…”
Section: Discussionsupporting
confidence: 88%
“…Regarding gender and survival, the overall survival for the male child was found to be better than the female child in a previous study,22 although no such association was observed among our patients. On multivariate analysis, stage of the disease (intraocular versus extraocular) had a significant impact on the survival outcomes, which is consistent with previous studies that reported an association between severity of disease and the survival outcome 9 27 28…”
Section: Discussionsupporting
confidence: 88%
“…The efficacy of chemotherapy was assessed within the context of a clinical cohort of patients with retinoblastoma described in detail elsewhere 6. Between January 2006 and December 2010, ophthalmologists in Uganda were invited to enter cases into the study while retaining management.…”
Section: Methodsmentioning
confidence: 99%
“…Between January 2006 and December 2010, ophthalmologists in Uganda were invited to enter cases into the study while retaining management. Some ophthalmologists in Uganda run mobile outreach teams, so cases came from all over the country; the degree of clinical investigation varied widely 6. At one centre (Ruharo Eye Hospital in Mbarara), recruitment continued throughout 2011.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Stage of the disease had a significant impact on the survival outcomes, which is consistent with previous studies that reported an association between severity of disease and the survival outcome. 21,33,34 The most feared complication of chemotherapy is the risk of developing other tumors in the medium and long term, particularly leukemia by use of Etoposide. 35 Radiation appears to have a higher incidence of non-ocular tumours.…”
Section: Discussionmentioning
confidence: 99%